The effect of polypropylene fiber on hardened and fresh properties of underwater geopolymer mortar - Ziada, Mahmoud; Tanyildizi, Harun; Coskun, Ahmet; Seloglu, Maksut (Ernst & Sohn, 2025)
In order to popularize the use of geopolymers, it is necessary to investigate the usability of geopolymers in water structures in or on the shores of seas and rivers. For this purpose, underwater geopolymer mortar with different percentages of polypropylene (PP) fiber was produced in this study. In the first stage, the effect of PP fiber on fresh underwater geopolymer mortar was investigated by performing slump and pH tests. In the next stage, mechanical tests were performed on the hardened mortars that were poured and waited underwater for 3, 7, and 28 days. Finally, microstructural analyses were carried out to verify the mechanical experiments and to examine the microstructural state of the underwater geopolymer mortar. As a result of this study, after 28 days, the compressive and flexural strengths of underwater geopolymer specimens containing 0.5% PP fiber were boosted by 3.90% and 210.75%, respectively, compared to the fiber-free underwater geopolymer specimens. In addition, the 28-day compressive strength achieved 53.05 MPa, demonstrating the geopolymer mortar's potential to achieve sufficient strength in a submerged condition. These findings underscore the viability of underwater geopolymer mortar for marine structures and other submerged building applications.
Keywords: mechanical properties; metakaolin; polypropylene fiber; underwater geopolymer